Service Organization – Evaluasi Kinerja Layanan Organisasi Nirlaba dengan Pendekatan Balanced Scorecard: Studi Kasus Lembaga Sosial di Indonesia - Arfa Mella Diva Intira; Cindi Aulia Silvianingsih; Anna Marina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Nonprofit organizations are increasingly utilizing Internet-based technologies to address accountability issues,playing a strategic role in social development in Indonesia. These organizations face increasingly complex challenges, including growing demands for transparency, accountability, and sustainability in fulfilling their missions .The Balanced Scorecard (BSC) approach, which includes four perspectives—financial, customer, internal business processes, and learning and growth—offers a comprehensive framework. The Balanced Scorecard connects intangible and tangible assets in value-creating activities A case study was conducted on a nationally scaled social organization in Indonesia. The results indicate that the BSC approach provides a holistic view of the organization's service efficiency and effectiveness. These findings contribute significantly to strengthening strategic evaluation systems and enhancing transparency and accountability in nonprofit management.